2022
DOI: 10.3390/diagnostics12051057
|View full text |Cite
|
Sign up to set email alerts
|

Negative mpMRI Rules Out Extra-Prostatic Extension in Prostate Cancer before Robot-Assisted Radical Prostatectomy

Abstract: Background: The accuracy of multi-parametric MRI (mpMRI) in the pre-operative staging of prostate cancer (PCa) remains controversial. Objective: The purpose of this study was to evaluate the ability of mpMRI to accurately predict PCa extra-prostatic extension (EPE) on a side-specific basis using a risk-stratified 5-point Likert scale. This study also aimed to assess the influence of mpMRI scan quality on diagnostic accuracy. Patients and Methods: We included 124 men who underwent robot-assisted RP (RARP) as pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Conducting research in non-academic, non-tertiary centers, where image quality is likely to be suboptimal, could determine how applicable this data is to less experienced institutions. The relationship between PI-QUAL and staging is also supported by Dinneen et al 117 Here, PI-QUAL scores ≥4 had a greater sensitivity and specificity for detecting EPE than scans scoring PI-QUAL ≤ 3, although the sample size was smaller. In contrast, recent studies have reported no significant difference between PI-QUAL ≥ 4 and PI-QUAL ≤ 3 scans in the ability to stage PCa 112 or detect EPE.…”
Section: Quality Assessmentsupporting
confidence: 70%
“…Conducting research in non-academic, non-tertiary centers, where image quality is likely to be suboptimal, could determine how applicable this data is to less experienced institutions. The relationship between PI-QUAL and staging is also supported by Dinneen et al 117 Here, PI-QUAL scores ≥4 had a greater sensitivity and specificity for detecting EPE than scans scoring PI-QUAL ≤ 3, although the sample size was smaller. In contrast, recent studies have reported no significant difference between PI-QUAL ≥ 4 and PI-QUAL ≤ 3 scans in the ability to stage PCa 112 or detect EPE.…”
Section: Quality Assessmentsupporting
confidence: 70%
“…Pre‐bioptic MRI and ROI targeting are recommended to complement systematic sampling during any reclassification biopsy 21 . It allows for accurate disease localization without biopsy‐related artifacts, and guides treatment for focal and radical therapies 22,23 …”
Section: Discussionmentioning
confidence: 99%
“…21 It allows for accurate disease localization without biopsy-related artifacts, and guides treatment for focal and radical therapies. 22,23 mpMRI may nevertheless miss some csPCa, and the search for other imaging modalities has continued with investigations on PSMA-PET and multiparametric US, even if less widely available than mpMRI. [24][25][26] The CADMUS trial showed that multiparametric US was noninferior to mpMRI in detecting csPCa defined as ISUP ≥ 2 disease, with a nonstatistically significant difference of 21.2% missed cancer by mpUS.…”
Section: Discussionmentioning
confidence: 99%
“…This is measured with the PI‐QUAL score, which reflects the extent to which the image assists in ruling in and ruling out clinically significant cancer 4,5 . Studies using the PI‐QUAL score have shown that DWI image quality, including SNR and resolution, significantly impacts the accuracy of cancer detection 6–9 …”
Section: Introductionmentioning
confidence: 99%